Peningkatan Keterampilan Mendengarkan Dongeng Siswa Kelas 1-B SD Negeri 2 Sokaraja Tengah Dengan Media Audio Visual - Mualifah, Siti (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2019)
This research is a classroom action research (PTK). The subjects are students of classI-B Elementary School 2 Sokaraja Tengah as many as 33 students, and the object ofthis study is a fairytale listening skills with audio-visual media. Data collectiontechniques in this study using observation and tests. Research instruments arepieces of observation and tests. The validity of the data is using triangulationtechniques, reference materials, and discussions with colleagues. The results of thisstudy show that (1) Audio-visual media can increase the activity of students of SDNegeri 2 Sokaraja Tengah in the learning process of hearing fairy tales. It can beseen on aspects of enthusiastic, attentive, active, determined, and in the spirit oflearning. (2) The use of audio-visual media can improve student learning outcomesin learning to listen to the fairy tales to the students of class I-B Elementary School 2Sokaraja Tengah. In pre cycle, the students who completed as many as 10 studentsor 30% and in the first cycle, students who completed as many as 24 students or 73%.In the second cycle, students who completed as many as 30 students or as many as91%.